2021
DOI: 10.1177/16094069211058009
|View full text |Cite
|
Sign up to set email alerts
|

‘We Do Not Talk About It’ – Exploring Visual Approaches to Initiate Deeper Conversations About Perinatal Mental Health With Indian Immigrants

Abstract: Exploring constructions of mental health in the perinatal period among Indian immigrants can be challenging. This article describes the use of visual methods, photo elicitation, free listing and pile sorting, as an adjunct to face-to-face interviews to understand the constructions of perinatal mental health among Indian immigrants in Australia. The benefits and challenges of using these methods and modifications made during the research are explained. The modifications resulted in a broader understanding of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The digital aspect of the MST tested in this study essentially adds “hands-on” and interactive online possibilities to the MST. The convergent study design, careful procedures, and the MSA analytic technique used in this study integrate the advances in mixed methods such as visual methodology (Fetters et al, 2013; Peroff et al, 2022), photo elicitation (Fearon, 2019; Kleih et al, 2022; Philip et al, 2021) and sorting (Yeh et al, 2014) for enriching the overall “understanding of the phenomena under analysis” (Onwuegbuzie and Dickinson, 2008 in Alexander et al, 2021). The MST procedure, including its digital version tested, distinguishes from those integrating qualitative and quantitative analyses that are carried out consecutively (Kleih et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital aspect of the MST tested in this study essentially adds “hands-on” and interactive online possibilities to the MST. The convergent study design, careful procedures, and the MSA analytic technique used in this study integrate the advances in mixed methods such as visual methodology (Fetters et al, 2013; Peroff et al, 2022), photo elicitation (Fearon, 2019; Kleih et al, 2022; Philip et al, 2021) and sorting (Yeh et al, 2014) for enriching the overall “understanding of the phenomena under analysis” (Onwuegbuzie and Dickinson, 2008 in Alexander et al, 2021). The MST procedure, including its digital version tested, distinguishes from those integrating qualitative and quantitative analyses that are carried out consecutively (Kleih et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This builds upon traditions in environmental psychology studies to incorporate visual material (i.e., colored pictures) within the general sorting method (Budhwar, 2000; Fiore et al, 2003; Groat, 1982; Wilson, 1996; Wilson and Mackenzie, 2000). The use of pictures is similar to photo elicitation and other visual methods and techniques (Fearon, 2019; Kleih et al, 2022; Philip et al, 2021), which helps to obviate possible language or culture barriers in studying ambiguous and/or stigmatized subjects. In the MST procedure, the participants are asked to sort pictures into groups in such a way that all pictures in one group are similar in some significant ways and different from those in other groups.…”
Section: Introductionmentioning
confidence: 99%
“…These words and phrases were given to the participants during the interview, and they were asked to sort these words into different piles as per their understanding. More details on these techniques and how they were applied in this study are reported in a previous publication (Philip et al, 2021). All interviews were audio-recorded with participants' consent and were then transcribed verbatim.…”
Section: Data Collectionmentioning
confidence: 99%
“…As the findings suggest, discussing mental health concerns by addressing the situational context may encourage women to identify and disclose mental health concerns, for example, enquiring if they are experiencing issues due to immigration and their experience of being pregnant in a new country. As discussed in our previous paper (Philip et al, 2021), it is also possible that these conversations about mental health could be assisted by tools such as images or phrases in the first language of the woman.…”
Section: Implications For Practicementioning
confidence: 99%
“…Approaching the online abuse with the concept of victim vulnerability first cited by (Fitzgerald et al, 1997) wherein the attacks on the public platform focus on the personalizedgendered and sexual aspects. Such comments used under the garb of freedom of expression often forget to shed any dignity on the person being trolled mercilessly [22].…”
Section: Theoretical Frameworkmentioning
confidence: 99%